Mechanical Properties of Cement Mortar after Dry–Wet Cycles and High Temperature - Liang-Xiao, Xiong; Xiao-Gang, Song (Salehan Institute of Higher Education, 2020)
The dry–wet cycle and high temperature exposure are important factors affecting the normal use and durability of concrete structures. The objective of this work is to investigate the mechanical properties of cement mortar specimens after combinations of dry–wet cycles and high temperature exposures, uniaxial compressive tests on cement mortar specimens were carried out under the following two sets of conditions: (1) high temperature treatment followed by a dry–wet cycle and (2) a dry–wet cycle followed by high temperature treatment. The results show that the compressive strength of specimens increases with the number of dry–wet cycles. After a dry–wet cycle and then a high temperature treatment procedure, the compressive strength of a specimen will first decrease and then increase with the number of dry–wet cycles. The strain at the peak stress of cement mortar decreases as the number of dry–wet cycles increases. At present, there are few research results about the mechanical properties of concrete first after combinations of dry–wet cycles and high temperature exposures. The work in this paper can enrich the results in this area.